CONTENIDO EN VITAMINA C DE FRUTAS MEXICANAS VITAMIN C CONTENT OF MEXICAN FRUIT - VIESCA, AMELIA; GIRAL, FRANCISCO (Laboratorio Zapata, CD MEXICO, DF, MEX, 1946)
The author describes 2 new squirrel-fleas from Mexico, Opisodasys robustus ssp mexicanus, Federal District, 2600 m, and Opisodasys perotensis, State of Veracruz, 3000 m He draws attention to the lack of homogeneity in the genus Opisodasys, where we can
CIENC MEX
Keywords: CONTENIDO, VITAMINA, FRUTAS, MEXICANAS; CIENCIAS MEDICAS; CIENCIAS DE LA NUTRICION; VITAMINAS